INTEREST RATES AND CURRENCIES EFFECTS ON ISLAMIC AND CONVENTIONAL BONDS - Ghazali Syamni; Husaini Husaini (Economic Journal of Emerging Markets, 2011)
Bond markets have not been well developed in emerging countries. Realizing its important role, especially after the 1997 crises and the islamic economics development, emerging countries have started to develop such markets. This research examines the effect of interest rates and currencies on Islamic and conventional bonds in Bursa Malaysia. The analysis on Islamic bonds shows that interest rates and currencies do not influence Islamic bonds, which supports the prohibition of interest in Islam. The analysis on conventional bonds finds evidence that both interest rates and currencies affect conventional bond. It also finds evidence of a negative association between interest rates and a conventional bond.